Analisa Faktor yang Mempengaruhi Tingkat Fertilitas (TFR) di Provinsi Maluku (Analisa Lanjutan Hasil SKAP 2019) - Marfin Lawalata; Jino Tehusalawane; Misco Tamaela; Marlon Stivo Noya van Delzen; Felecia P Adam (Universitas Medan Area, 2022)
The purpose of this study was to determine the determinants of the factors causing the high Fertility Rate (TFR), rs that affect the number of children born alive. The data used is SKAP data in 2019, with a respondent of women of childbearing age aged 15-49 years. With the model used is binary logistic regression analysis. The results showed that 12 variables had a significant relationship with live births. Child mortality is the most dominant variable that has a significant effect on the number of children born alive, Recommendations that can be given from the results of this study are to increase the supervision of the Health Office related to strengthening institutional capacity through counseling / communication, information, and education through postponement of marriage age and first birth age programs. first age relationship and education about early childhood sex through adolescent reproductive health counseling in order to increase knowledge, attitudes, and behavior of families and communities to create a quality family.